2010
DOI: 10.1152/ajpregu.00584.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptors: what's new and what do we need to know?

Abstract: Receptors are at the heart of how a molecule transmits a signal to a cell. Two receptor classes for endothelin (ET) are recognized, the ET(A) and ET(B) receptors. Intriguing questions have arisen in the field of ET receptor pharmacology, physiology, and function. For example, a host of pharmacological studies support the interaction of the ET(A) and ET(B) receptor in tissues (veins, arteries, bronchus, arterioles, esophagus), but yet few have been able to demonstrate direct ET(A)/ET(B) receptor interaction. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 120 publications
1
56
0
3
Order By: Relevance
“…34 The ET A receptor belongs to G protein-coupled receptors, and its downstream signals require Gq. 35 Data from the present study suggest that estradiol-mediated protective stress-kinase programs modulated induction of the maladaptive calcineurin pathway, which was responsible for a mild and adaptive cardiac phenotype in female mice with intact ER␤. In vitro data, in which the antihypertrophic effect of an ER␤ agonist was similar to that of estradiol in ET-1-stimulated female mouse cardiomyocytes, were consistent with this idea.…”
Section: Discussionmentioning
confidence: 59%
“…34 The ET A receptor belongs to G protein-coupled receptors, and its downstream signals require Gq. 35 Data from the present study suggest that estradiol-mediated protective stress-kinase programs modulated induction of the maladaptive calcineurin pathway, which was responsible for a mild and adaptive cardiac phenotype in female mice with intact ER␤. In vitro data, in which the antihypertrophic effect of an ER␤ agonist was similar to that of estradiol in ET-1-stimulated female mouse cardiomyocytes, were consistent with this idea.…”
Section: Discussionmentioning
confidence: 59%
“…Novel aspects on ET receptor pharmacology can be found in two very elegant articles by Dr. Stephanie Watts (166) and Dr. Erika Boesen (11). These authors focused on the interactions between ET receptors (formation of heterodimers and homodimers, which may explain some puzzling results from receptor-binding and functional studies) (11,166), the possibility of differential signaling or biased agonists (that different agonists can elicit different signal transduction events through the same receptor), and interactions of components of the ET system with other molecules, e.g., the dual angiotensin II-ET receptor and the Parkinassociated ET receptor-like receptor (where the ET receptor B-like protein receptor 1 functions as a substrate for Parkin, a polypeptide with similarities to ubiquitin protein ligase E3) (166).…”
Section: (Signaling Pathways Activated By Et-1 That Can Be Modified Bmentioning
confidence: 99%
“…They will be referred to excellent reviews on O-GlcNAcylation (54,55,63,84,90,110,167,169,177). Detailed information on ET peptides, ET receptors, ET signaling, models for the study of ET in disease conditions, and development and therapeutic use of ET A /ET B receptor antagonists can be found on excellent and more comprehensive reviews on these specific topics (6,8,11,12,30,31,34,37,67,79,81,115,122,131,141,142,154,160,166).…”
mentioning
confidence: 99%
“…50 Once ET-1 binds to its receptor (Gq-proteins) on the vascular smooth muscle it induces an increase in inositol 1,4,5-triphosphate levels, with subsequent calcium release and muscle contraction. 50 Specifically, it has been shown that EC dysfunction and inflammation contribute to an overproduction of ET-1 in humans. 52 The exact role of ET-1 in VTE, however, remains unclear.…”
Section: Platelet-activating Factormentioning
confidence: 99%